2018
DOI: 10.1089/trgh.2018.0005
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus and Trans Women: A Literature Review

Abstract: Trans women are a key, yet under-researched, population in the HIV epidemic. However, there remains a paucity of data on the health and wellbeing of trans women at risk of, or living with, HIV in the United Kingdom. This article provides a narrative review of key empirical research into HIV among trans women. In an effort to explore individual and social factors in relation to HIV in this population, we outline key tenets of identity process theory from social psychology and the concept of structural violence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 71 publications
(87 reference statements)
0
15
0
1
Order By: Relevance
“…Conversely, a USA study found gender-specific discrimination was associated with sexual risk behaviours, but not HIV testing among trans people 14. A literature review on trans women and HIV identified a lack of UK data and research,15 which is concerning considering trans people in England are twice as likely to be diagnosed with HIV at a late stage than cisgender people 16. Research into barriers and psychosocial factors affecting access to sexual healthcare and HIV testing for trans people is needed to inform health promotion.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a USA study found gender-specific discrimination was associated with sexual risk behaviours, but not HIV testing among trans people 14. A literature review on trans women and HIV identified a lack of UK data and research,15 which is concerning considering trans people in England are twice as likely to be diagnosed with HIV at a late stage than cisgender people 16. Research into barriers and psychosocial factors affecting access to sexual healthcare and HIV testing for trans people is needed to inform health promotion.…”
Section: Introductionmentioning
confidence: 99%
“…We explored changes in sexual behaviour and use of SHS among cisgender men, transgender and gender-diverse people who have sex with men in the UK, during the UK COVID-19 response to understand service need. The paucity of evidence on sexual risk behaviours among transgender and gender-diverse people in the UK [10][11][12] underlines the importance of identifying the sexual health needs of these groups. 13 Previous research demonstrated the feasibility and acceptability of rapid risk assessment methods to enhance existing surveillance measures in response to public health incidents and outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…Trans people and in particular trans women are a key population at increased risk of HIV acquisition, yet are severely underserved in the global response, including in HIV prevention and testing research [ 2 , 3 ]. There is also a lack of data on the sexual health needs of trans men and women in the UK, despite the fact that this group is more likely to be diagnosed with HIV late, less likely to attend sexual health clinics and less likely to test for HIV than cisgender men who have sex with men (MSM) [4] , [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%